Abiotic conditions from the local environment of Arctic kelp populations on the west coast of Svalbard, Norway - Sarina Niedzwiedz; Clara Voigt; Sebastian Andersen; Nora Diehl; Børge Damsgård; Kai Bischof (PANGAEA, 2025)
We assessed how Arctic kelp populations react to their local in situ environment in August 2022. Therefore, we sampled Saccharina latissima sporophytes from eight populations at several latitudes on the west coast of Svalbard, Norway, and correlated these results to the abiotic conditions they experienced. Data was smoothed by the mean for every meter interval. We measured the spectrally resolved underwater light climate from 400-700 nm with a RAMSES-ACC-UV/VIS radiometer (TriOS Optical Sensor, Oldenburg, Germany) from the surface until the bottom was reached (max. 10 m). The photosynthetically active irradiance (PAR) was calculated by integrating the irradiance. The light attenuation coefficient (Kd) was calculated between the surface and 3 m water depth. The spectrum peak (nm) on 3 m water depth was defined as the wavelength with the maximum irradiance transmission through the water column.